Multilingual and Bi-dialectal Irony Processing - Antoniou, Kyriakos (My University, 2022)
We examined the effects of multilingualism and bi-dialectalism on irony interpretation by comparing multilingual, bi-dialectal, and monolingual young adults. We used an act-out task with three Meaning (literal positive, literal negative, ironic) and four Cue conditions (context-only, intonation-only, intonation + face, context + intonation + face). Results revealed that irony interpretation was (1) difficult, as shown by slower and less accurate responses to ironic compared to literal items; (2) facilitated by the presence of more ironic cues. Moreover, evidence suggested that linguistic context had a greater and facilitative effect on the speed of irony processing compared to literal meanings. Finally, we found no evidence for group differences in accuracy or speed of irony processing or in the way that different (combinations of) cues affected irony. Overall, our findings support a view of multilingual pragmatics according to which pragmatic interpretation is no different in multilinguals compared to monolinguals.
Keywords: dialects; irony; multilingualism; pragmatics